What Lies Inside a Dead Coral: Diversity of Reef-Associated Cryptic Crustacean (Crabs: Anomura and Brachyura) from Different Habitat Characteristics in Tidung Islands, Indonesia - Satya Pratama Atmaja; Prakas Santoso; Muhamad Gilang Arindra Putra; Fadel Muhammad; Wiwid Andriyani Lestariningsih; Beginer Subhan; Hawis Madduppa (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research The very first attempt to investigated and revealing biodiversity of crustacean crab in coral reef ecosystem at Tidung Island, Indonesia Conservation area (Tidung Kecil) has more abundant crab species than tourism area (Tidung Besar). A microhabitat that suffers anthropogenic pressure may alter the composition of crustacean biodiversity, especially in crab group. Different characteristics and complexity of coral habitat affect the dynamics of cryptic crustacean communities Abstract Recent studies have been widely carried out on the important role and ecological function of coral reefs. However, little attention has been given to small and cryptic crustaceans organisms living within different microhabitat in dead corals. This study aimed to reveal the diversity of crustaceans that inhabit dead corals in Tidung Islands, Indonesia. A total of 134 individuals from 41 species in 13 families were recorded within eight dead corals taken from two different sites. Furthermore, the species identified from Tidung Kecil were significantly different and more diverse than Tidung Besar. It was suggested that differences in anthropogenic pressure between Tidung Besar and Kecil might have an important role in the spread of crab crustaceans' organisms. Xanthidae from infraorder Brachyura were observed to be the most dominant family, while Galatheidae and Porcellanidae from infraorder Anomura spread almost equally in both sites. Additionally, Psaumis cavipes and Chlorodiella nigra were species with the largest contribution of crab crustaceans' communities in the death of coral's ecosystem in the Tidung Islands. This result indicated that dead corals might play a key role in supporting and providing a habitat for crustacean cryptic.